Crystal structure of (E)-(3-(2,4-dichlorophenyl)acryloyl)ferrocene, C19H14Cl2FeO - Zhang Shuang; Gao Jie; Wen Juanjuan; Gao Yanrong; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures)
C19H14Cl2FeO, monoclinic, P21/n (no. 14), a = 7.3383(5) Å, b = 10.1441(6) Å, c = 21.4807(12) Å, α = 90 Å, β = 91.649(2) Å, γ = 90 Å, V = 1,598.37(17) Å3, Z = 4, Rgt(F) = 0.0443 wRref(F2) = 0.1132, T = 183 K.